Evaluating metal bioaccessibility of soils and foods using the SHIME - Laird, Brian Douglas (University of Saskatchewan, 2010)
Ingestion exposure estimates typically use a default bioavailability of 100%, thereby assuming that the entirety of an ingested dose is absorbed into systemic circulation. However, the actual bioavailability of ingested contaminants is oftentimes lower than 100%. The research described herein investigates the use of the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) for the calculation of in vitro bioaccessibility (IVBA), a conservative predictor of bioavailability, of mercury (Hg) from traditional northern foods and arsenic (As) from soils. The primary objective of the research described herein is to address data-gaps which have hindered attempts to incorporate IVBA into risk assessment on more than a case-by-case basis. The hypotheses of this thesis are that (1) the bioaccessibility of contaminants is dependent upon concentration due to kinetic limitations on dissolution, (2) gastrointestinal (GI) microbes in the ileum and colon alter contaminant bioaccessibility and/or speciation, (3) the GI microbial effect on bioaccessibility is toxicologically relevant, and (4) metal bioaccessibility is predictable according to dissolution kinetics. Mercury bioaccessibility from country food samples was independent of total Hg concentration (F=0.5726, P=0.578) whereas As bioaccessibility was inversely related to total As concentration for Nova Scotia mine tailings, synthesized ferrihydrite with adsorbed AsV, and synthesized amorphous scorodite (P=2 x 10-10). Isotherm analysis indicated that, at high soil As concentrations, saturation of simulated GI fluids limited As bioaccessibility under gastric conditions whereas kinetic limitations constrained As bioaccessibility under intestinal conditions. Additionally, we demonstrated that GI microbes may affect Hg bioaccessibility, either increasing or decreasing bioaccessibility depending upon the type of food. For example, the bioaccessibility of HgT decreased in the presence of GI microbial activity for caribou kidney, caribou tongue, seal blood, seal brain, seal liver, and walrus flesh. In contrast, HgT bioaccessibility from Arctic char and seal intestine increased in the presence of GI microbial activity. Similarly, colon microbial activity increased (Fishers Protected LSD, P